Double aberration correction in a low-energy electron microscope - Schmidt, Th; Marchetto, H.; Levesque, P. L.; Groh, U.; Maier, F.; Preikszas, D.; Hartel, P.; Spehr, R.; Lilienkamp, G.; Engel, W.; Fink, Rainer; Bauer, E.; et al. (Ultramicroscopy, 2010)
The lateral resolution of a surface sensitive low-energy electron microscope (LEEM) has been improved below 4. nm for the first time. This breakthrough has only been possible by simultaneously correcting the unavoidable spherical and chromatic aberrations of the lens system. We present an experimental criterion to quantify the aberration correction and to optimize the electron optical system. The obtained lateral resolution of 2.6. nm in LEEM enables the first surface sensitive, electron microscopic observation of the herringbone reconstruction on the Au(1. 1. 1) surface. © 2010 Elsevier B.V.